2016
DOI: 10.1038/srep37065
|View full text |Cite
|
Sign up to set email alerts
|

Exploring time- and frequency- dependent functional connectivity and brain networks during deception with single-trial event-related potentials

Abstract: To better characterize the cognitive processes and mechanisms that are associated with deception, wavelet coherence was employed to evaluate functional connectivity between different brain regions. Two groups of subjects were evaluated for this purpose: 32 participants were required to either tell the truth or to lie when facing certain stimuli, and their electroencephalogram signals on 12 electrodes were recorded. The experimental results revealed that deceptive responses elicited greater connectivity strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 56 publications
(112 reference statements)
0
9
0
1
Order By: Relevance
“…The brain is a complex system in which the dynamic adjustment of network organization over multiple time scales is crucial for mediating perception and cognition2223242526272829303132. Characterizing the dynamics of brain FC or properties of network topology is thought to be important for gaining a better understanding of brain function and behavioural performance13333435.…”
mentioning
confidence: 99%
“…The brain is a complex system in which the dynamic adjustment of network organization over multiple time scales is crucial for mediating perception and cognition2223242526272829303132. Characterizing the dynamics of brain FC or properties of network topology is thought to be important for gaining a better understanding of brain function and behavioural performance13333435.…”
mentioning
confidence: 99%
“…In addition, Seth et al [17] reported that the alpha activities exhibited a significant decrease during deception, which could be used to classify truthful and deceptive responses on a trial-by-trial basis. Further, Gao et al [18] proposed that, at the system level, the connectivities between the prefrontal/frontal and central regions and between the prefrontal/frontal and left parietal regions play crucial roles in the processing of deception. Particularly, high theta synchronization was observed primarily in the abovementioned networks during deception [18].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Gao et al [18] proposed that, at the system level, the connectivities between the prefrontal/frontal and central regions and between the prefrontal/frontal and left parietal regions play crucial roles in the processing of deception. Particularly, high theta synchronization was observed primarily in the abovementioned networks during deception [18]. Thus, the frequency components and high level of synchronization between different regions in a specific frequency band may functionally reflect a transient change in the system process of deception.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Então, cada vez mais com o avanço das tecnologias, diversos estudos científicos vêm sendo realizados utilizando-se de outras técnicas que têm se mostrado promissoras para a área da detecção de mentiras. Por exemplo, a Termografia (Panasiti et al, 2016;Moliné et al, 2017), Eletroencefalograma (Gao et al, 2016;Kohan, Nasrabadi, Sharifi & Shamsollahi, 2020) e Ressonância Magnética Funcional (Farah, Hutchinson, Phelps & Wagner, 2014;Kireev, Korotkov, Medvedeva, Masharipov & Medvedev, 2017).…”
Section: Medidas Fisiológicasunclassified